The Longue Durée of Empire : : toward a comperative semantics of a key concept in modern European history - Leonhard, Jörn (2013)
Abstract: Against the background of a new interest in empires past and present and an inflation of the concept in modern political language and beyond, the article first looks at the use of the concept as an analytical marker in historical and current interpretations of empires. With a focus on Western European cases, the concrete semantics of empire as a key concept in modern European history is analyzed, combining a reconstruction of some diachronic trends with synchronic differentiations